Habits, Rationality and Myopia in the Life-Cycle Consumption Function. - Muellbauer, J (CEPR, 1986)
This paper investigates the role of habits in the consumption function. Two types of habits are considered: rational and myopic, these being distinctions which have long been made in the literature on systems of demand equations. In both cases past consumption affects current preferences, thus breaking the intertemporal separability of preferences often assumed by economists. If habits are rational, consumers are aware of the effect of their current consumption decisions on their future marginal rates of substitution. If habits are myopic, consumers lack this awareness and this may result in a time inconsistency in their behaviour. We explore the consequences of these two types of habituation, both for traditional "solved-out" consumption functions and for consumption functions in the "Euler equation" form popularized by Hall (1978). The two types of habitual behaviour yield representations of the aggregate consumption function which are in principle observationally distinct. We estimate the Euler-equation form of the consumption function for quarterly United States data over the period 1954-1981. We also consider time aggregation and other specification issues, such as those posed by liquidity constraints.